2022
DOI: 10.2147/ppa.s376557
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Practice and Its Associated Factors Among Podoconiosis Patients in East Gojjam Zone, North West Ethiopia

Abstract: Introduction Podoconiosis is endemic non-filarial elephantiasis of the lower legs swelling caused by barefoot exposure to red clay soil. The burden of disability occurs among the poorest populations. Self-care practice is the most cost-effective prevention strategy practiced at home to improve lymphedema, working functionality, and quality of life. Despite this, there is a scarce of knowledge about self-care practices and associated factors among podoconiosis patients in Ethiopia. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The study by Esubalew et al (2022) indicated that self-care in patients with podoconiosis was not well performed, and since social and demographic factors are known as factors related to self-care performance, strengthening health education and behavioral changes is necessary to improve self-care performance [22].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Esubalew et al (2022) indicated that self-care in patients with podoconiosis was not well performed, and since social and demographic factors are known as factors related to self-care performance, strengthening health education and behavioral changes is necessary to improve self-care performance [22].…”
Section: Discussionmentioning
confidence: 99%